VALIDATION AND CULTURAL ADAPTATION OF THYPRO (THYROID PATIENT REPORTED OUTCOME) QUESTIONNAIRE IN BAHASA (INDONESIAN LANGUAGE): A PRELIMINARY STUDY - Pramono, Laurentius Aswin; Putranto, Rudi; Rizka, Aulia; Subekti, Imam (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES The Thyroid Patient Reported Outcome (ThyPRO) questionnaire is a specific tool to assess health-related quality of life of patients with thyroid diseases. The aim of this study is to determine the validity and reliability of ThyPRO questionnaire among patients with Graves’ disease in Bahasa (Indonesian language). METHODOLOGY This is a preliminary study among patients with Graves’ disease in Cipto Mangunkusumo Hospital, a national referral hospital in Jakarta, Indonesia. After a systematic two-way translation process, the questionnaire was adapted and culturally validated. Internal reliabilities of the ThyPRO scales were assessed using Cronbach’s α coefficient. RESULTS Twenty patients with Graves’ disease completed the questionnaire process. Internal consistency and reliability of the ThyPRO scales were good. Test-retest reliability was done by calculating intraclass correlation coefficient (ICC) for each of the items and domains of the ThyPRO questionnaire. The ICC was moderate (ICC between 0.5 – 0.75) and reliability was good (ICC score >0.75). CONCLUSION The ThyPRO may be a useful, valid, and reliable tool for measuring health-related quality of life among patients with Graves’ disease in Indonesia.